DRP2 promotes EMT and serves as a potential therapeutic target for LUAD treatment - Zhimeng Chen; Hao Shi; Wenxuan Hu; Jian Yang; Yuxuan Xing; Xin Lv; Chenzhuo Wu; Cheng Ding; Jun Zhao (Scientific Reports)
Abstract LUAD, a prevalent lung cancer with high mortality, has seen increased focus on molecular targeted therapies due to patient heterogeneity. Among these prospects, dystrophin-associated protein 2 (DRP2), a critical component of the dystrophin complex, underpins membrane-associated structures vital for intercellular interactions in vertebrates. Aberrations in DRP2 function have been linked to the occurrence and development of multiple diseases, prompting an inquiry into its potential link with LUAD progression. To delve into the potential roles of DRP2 in LUAD, we initiated a comprehensive investigation. First, we analyzed DRP2 expression patterns in LUAD using bioinformatics tools. This was subsequently validated through immunohistochemical staining, quantitative PCR, and Western blot analyses. Furthermore, we assessed the functional implications of DRP2 in LUAD cells, both in vitro and in vivo, utilizing assays such as cell cycle analysis, CCK-8 proliferation assay, Colony formation assay EdU incorporation, Transwell migration test, scratch wound healing assay, flow cytometry, and mouse models for tumor xenograft and metastasis. Results showed a strong correlation between high DRP2 expression in LUAD and poorer survival. Notably, DRP2 knockdown accelerated LUAD progression via the EMT pathway. These findings highlight DRP2’s crucial role in LUAD and its potential as a therapeutic target.